Acceleration of cancer science with genome editing and related technologies. Issue 12 (31st October 2018) - Sakuma, Tetsushi; Yamamoto, Takashi
Abstract : Genome editing includes various edits of the genome, such as short insertions and deletions, substitutions, and chromosomal rearrangements including inversions, duplications, and translocations. These variations are based on single or multiple DNA double‐strand break (DSB)‐triggered in cellulo repair machineries. In addition to these "conventional" genome editing strategies, tools enabling customized, site‐specific recognition of particular nucleic acid sequences have been coming into wider use; for example, single base editing without DSB introduction, epigenome editing with recruitment of epigenetic modifiers, transcriptome engineering using RNA editing systems, and in vitro detection of specific DNA and RNA sequences. In this review, we provide a quick overview of the current state of genome editing and related technologies that multilaterally contribute to cancer science. Abstract : In addition to conventional genome editing strategies, tools enabling customized, site‐specific recognition of particular nucleic acid sequences have been coming into wider use; for example, single base editing without DSB introduction, epigenome editing with recruitment of epigenetic modifiers, transcriptome engineering using RNA editing systems, and in vitro detection of specific DNA and RNA sequences. In this review, we provide a quick overview of the current state of genome editing and related technologies that multilaterally contribute to cancer science.